Applying a combination of laboratory X-Ray diffraction and digital image correlation for recording uniaxial stress-strain curves in thin surface layers. (1st October 2020) - Smith, A.D.; Warren, J.; Harrison, G.; Blackmur, M.S.; Morse, S.; Wilford, K.; Preuss, M.
Highlights: Combination of surface sensitive stress and strain measurement techniques. Validated against standard mechanical testing. Measured surface properties represented bulk properties. Applicable to measuring insitu behaviour of coatings and other surface treatments. Abstract: By combining laboratory-based x-ray diffraction stress analysis with optical digital image correlation recorded in-situ during tensile loading, a new methodology has been developed to obtain for surface specific stress-strain curves. This novel methodology has been validated by comparing the reconstructed stress-strain curves from the x-ray diffraction/optical digital image correlation approach with stress-strain curves recorded using standard methods. The validated methodology enables now the recording of standard mechanical test data of altered surface layers, such as shot peened and machined surfaces or from proton-irradiated samples where the irradiated layer is limited to a depth of 10 s of microns. Graphical abstract: Image, graphical abstract